Measuring the Total Quality Management in the Indonesian Universities: From the Perspectives of Faculty Members - Mohamed, Abdulsalam Omar Lamin, Prof. Dr. Bambang Setiaji, Drs. M. Farid Wajdi, MM., Ph.D (2014)
The purpose of this study was to develop a tool to measure the degree of meeting the principles of Total Quality Management in higher education institutions, and included this tool or measure being distributed to the four core areas in Total Quality Management. The study population included all faculty members holding doctorates and master's Universities in Indonesia. The study sample was stratified random sample was selected to suit the size and the way identified with the requirements of scientific methodology. Statistical references have been identified by the sample size (100). The 95% confidence level, has been distributing a number of forms to each faculty commensurate with the number of faculty members, where with the total number of faculty members in universities. Researchers distributed a questionnaire to the various faculties of universities has recovered 100 form. The results obtained showed that: Variables are jointly independent (dimension of the field of organizational culture; dimension of the academic field; dimension of the area of professional growth, and dimension of the field of university relationship with the local community) significant influence on the dependent variable (total quality management).